2014
DOI: 10.1007/s00393-014-1527-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological defensive profile of sciatica patients with neuropathic pain and its relationship to quality of life

Abstract: The acting out defensive style and BDI were independently associated with pain-related quality of life. In the SNP group, significant differences were found in the immature and neurotic styles of the defense mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
3
5
0
Order By: Relevance
“…The present study shows that patients with NP display a number of differences when compared to age‐ and sex‐matched healthy volunteers. Patients with NP are more depressed and anxious ( P < 0.001) and show a diminished quality of life ( P < 0.001) compared to controls, confirming reports in the literature . Patients with NP also present some degree of cognitive impairment for vigilance, spatial planning/working memory, speed of movement, decision making, risk‐taking behavior, and semantic memory, as already reported in patients with chronic pain .…”
Section: Discussionsupporting
confidence: 86%
“…The present study shows that patients with NP display a number of differences when compared to age‐ and sex‐matched healthy volunteers. Patients with NP are more depressed and anxious ( P < 0.001) and show a diminished quality of life ( P < 0.001) compared to controls, confirming reports in the literature . Patients with NP also present some degree of cognitive impairment for vigilance, spatial planning/working memory, speed of movement, decision making, risk‐taking behavior, and semantic memory, as already reported in patients with chronic pain .…”
Section: Discussionsupporting
confidence: 86%
“…In a study on patients with chronic illness, the researchers concluded that patients showed an immature defense and neurological profile (25). Also, in sciatica patients, the findings showed that exponential action of defense-style and depression with pain related to QoL were correlated and in these patients immature and neurotic defensive profile was diagnosed from defense mechanisms (29). Another finding of this study was that excessive use of reaction formation and projection mechanisms are associated with lower levels of QoL in the cognitive and role aspects.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research of patients with and without NP based on clinical examination, [33][34][35] which found fewer differences in pain duration, LBLP-related disability, depression, anxiety, and health-related quality of life between patients with and without NP compared with those research studies using screening tools to identify cases of NP. [36][37][38] None of the previous studies [33][34][35][36][37][38] aimed to describe the characteristics of LBLP patients with or without NP and, in part, were limited by either small sample sizes or poorly defined comparator groups.…”
Section: Discussionmentioning
confidence: 99%